Fu brick tea alleviates high fat induced non-alcoholic fatty liver disease by remodeling the gut microbiota and liver metabolism - Tang, Yan; Chen, Bowei; Huang, Xin; He, Xu; Yi, Jian; Zhao, Hong; Tian, Fengming; Liu, Yingfei; Liu, Baiyan (Frontiers in Nutrition, 2022)
Fu brick tea (FBT) and its extracts have good lipid-lowering effects and have been used in the treatment of obesity in previous studies. Unfortunately, the therapeutic effect of FBT on non-alcoholic fatty liver disease (NAFLD) has not been thoroughly studied. In this study, we explored the mechanism by which FBT alleviates NAFLD from the perspective of the gut microbiota and liver metabolites. The results showed that FBT could reduce the body weight, liver weight and abdominal fat of NAFLD mice, and improve liver pathological morphology, liver lipid deposition, blood lipids and liver function. Moreover, FBT improved the diversity of the gut microbiota and changed the profile of liver metabolism in NAFLD mice. Further studies showed that FBT could ameliorate the cecum barrier, and regulate the effects of factors related to lipid synthesis in the cecum and liver of NAFLD mice. In conclusion, the present study confirmed that FBT can alleviate high fat induced NAFLD by regulating the homeostasis of the gut microbiota and liver metabolites.